PENINGKATAN PROFESIONALISMEN GURU MELALUI MANAJEMEN PENDIDIKAN ISLAM PADA GENERASI ALPHA DI MIS ELSUSI MELDINA - Naldi, Anri; Hasman, Haryaji Catur Putera; Rusdi, Muhammad; Nasution, Nurdila; Dasriansyah, Dasriansyah (Universitas Negeri Medan, 2024)
The lack of training and utilization of technology-based digital learning media is problematic in improving teacher professionalism in educating the current generation of Alfha at MIS Elsusi Meldina. Through the Community Service Partnership Program as a form of the Tridarma of Education. Seeing the condition of these problems offers solutions: 1. Professional Improvement of Teachers through Islamic Education Management 2. Professional Improvement of Teachers through the use of technology-based digital media in learning. The results showed that the lack of knowledge and training followed in improving teacher professionalism has hampered the course of education management, both from policy factors, leadership, supervision and supervision that are not carried out properly. So that with the number of educators and education staff of 16 people and the number of students 412 currently experiencing several problems caused by lack and lack of knowledge, digital medians, mastery of technology in learning, this is a big barrier in improving their professionalism in the learning process. It was concluded that the community service activities carried out for six months have brought changes in improving teacher professionalism through the management of Islamic education in the alfha generation as shown by the improvements made by Mis Elsusi Meldina both in teacher professionalism, through training and knowledge, Islamic education management through improving policies, leadership, verification and supervision and educating the alfha generation using media, digital and technology-based learning models.